Community structure of mangroves at Brgy. Tabucan, Manduriao, Iloilo City. - Castillano, Jane Laxinto
The mangroves of the Philippines have been declining over the past years due to a range of anthropogenic pressures. Certain actions have been taken by local communities, like mangrove reforestation projects, to preserve these mangrove areas. The purpose of this study is to determine the mangrove community structure of the mangrove reforestation site at Brgy. Tabucan, mandurriao, Iloilo City. The study was conducted in March 2011 using line plot method. Five plots were randomly distributed in the area. Water tenperature, water salinity, water pH, soil temperature, and soil pH were found to be on an average of 28.7 degrees centigrade, 23 ppt, 8.52, 30 degrees centigrade, and 7.31, respectively. Soil substrate at the site was generally muddy. Avicennia marina and Sonneratia alba were the species present in the area. The total seedling count was 154 and the total sapling count was 91. Avicennia marina had a higher seedling count (138), sapling count (69), stand basal area (1.92 msquared/ha.), stem per hectare (16,560 stems/ha), relative density (84.49 percent), relative frequency (55.56 percent), relative dominance (77.14 percent), and importance value (217.19). On the other hand, Sonneratia alba had a lower seedling count (16), sapling count (22), stand basal area (0.58 m squared/ha), stem per hectare (3,040 stems/ha), relative density (15.51 percent), relative frequency (44.44 percent), relative dominance (22.86 percent), and importance value (82.81). No zonation was observed in the area. The diversity of mangroves at the area using the Shannon Index was 0.26. This is lower compared to other mangrove sites which were already studied and assessed of their diversity. This can be attributed to the location of the site where there is no observed water movement or tidal inundation, which also means there is minimal disturbance on the area. It is highly recommended that maintenance of the mangrove reforestation site must be continued and monitored.